2008
DOI: 10.1007/s10620-007-0141-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress, Inflammation and Neutrophil Superoxide Release in Patients with Crohn’s Disease: Distinction Between Active and Non-active Disease

Abstract: Increased oxidative stress has been previously demonstrated in patients with Crohn's disease (CD). However, to date, this parameter has not been assessed in a comparative study of patients in prolonged remission and those with the active disease. We report here our study of lipid peroxidation, antioxidant and inflammation status in serum derived from 16 active CD patients, 27 clinically stable patients, and 15 healthy controls. Results The extent of lipid peroxidation was higher in CD patients than in the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
3
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 33 publications
(32 reference statements)
6
39
3
1
Order By: Relevance
“…Increased ROS affects intracellular signals that regulate processes such as cell growth, differentiation and cell death, and increases oxidative stress [11,12]. In studies conducted in Crohn's disease patients it has been shown that oxidative stress is increased by ROS during the activation period [13,14]. In another study done by Maor et al, it was found that oxidative stress increases while the antioxidant capacity decreases during the activation period of Crohn's disease [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased ROS affects intracellular signals that regulate processes such as cell growth, differentiation and cell death, and increases oxidative stress [11,12]. In studies conducted in Crohn's disease patients it has been shown that oxidative stress is increased by ROS during the activation period [13,14]. In another study done by Maor et al, it was found that oxidative stress increases while the antioxidant capacity decreases during the activation period of Crohn's disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in Crohn's disease patients it has been shown that oxidative stress is increased by ROS during the activation period [13,14]. In another study done by Maor et al, it was found that oxidative stress increases while the antioxidant capacity decreases during the activation period of Crohn's disease [13]. Bilirubin is a product of HEM destruction, which is catalyzed by the HO enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced oxidative stress and inflammation in conjunction with decreased antioxidant levels have been reported in patients with active Crohn's disease. However, with improvement of the patient's condition, these parameters of oxidative stress go back to normal levels (178). As NF-B is a major inducer of inflammatory cytokines, the effect of a potent NF-B inhibitor, vanillin, has been studied in mouse model of colitis (325).…”
Section: Ibds (Ulcerative Colitis Crohn's Disease)mentioning
confidence: 99%
“…However, enhanced inflammatory and oxidative stress and a decreased antioxidant status were shown in patients with active CD. As the patients improve and become clinically stable, the oxidative parameters decrease, approaching normal values [2]. This is why it is not easy to conclude ''reduced neutrophil count rather than a function'' with these study patients.…”
mentioning
confidence: 82%